Language, Culture, and Collectivism: Uniting Coalition Partners and Promoting Holistic Health in the Menominee Nation. (October 2019) - Hilgendorf, Amy; (Guy Reiter), Anahkwet; Gauthier, Jennifer; Krueger, Scott; Beaumier, Kimberly; Corn, Ron; Moore, Travis R.; Roland, Hugh; Wells, Alexandra; Pollard, Ethen; Ansell, Sara; Oshkeshequoam, James; et al.
Recent perspectives on Indigenous health have recognized language, culture, and values as central to well-being and recovery from historical trauma. Health coalitions, which identify community health concerns and mobilize members to implement strategies for change, have begun to shift their focus from programs to policy, systems, and environmental change but have been slower to recognize the possibilities of centering Indigenous ways of being in their work. This article details a case study of the Menominee Wellness Initiative, an Indigenous health coalition that has increasingly made language, culture, and collective values the focus of their health promotion work, and often due to the participation and influence of community organizers in the coalition. The study is presented as a collaborative writing effort between coalition members and academic partners. Qualitative data were gathered through observations of coalition meetings; in-depth, semistructured interviews with coalition members; and interactive data analysis discussions within the collaborative writing team. In the results, we describe how the shift in the coalition's framework came to be and the influence this shift has had on the coalition, its activities, and its community impacts. These findings illustrate and extend understanding of several principles of Collaborating for Equity and Justice and supports literature and practice related to health promotion through the centering of Indigenous ways.